Big Data Analysis: Apache Spark Perspective (Global Journal of Computer Science and Technology, 2015)
Big Data have gained enormous attention in recent years. Analyzing big data is very common requirement today and such requirements become nightmare when analyzing of bulk data source such as twitter twits are done, it is really a big challenge to analyze the bulk amount of twits to get relevance and different patterns of information on timely manner. This paper will explore the concept of Big Data Analysis and recognize some meaningful information from some sample big data source, such as Twitter twits, using one of industries emerging tool, known as Spark by Apache.
Keywords: big data analysis; twitter; apache spark; apache hadoop; open source